Copoiesis: Mutual knowledge creation in alliances - Ricarda B. Bouncken; Robin Pesch; Andreas J. Reuschl (Journal of Innovation & Knowledge (JIK), 2016)
Access and utilization of knowledge as in alliances drives firm performance. Prior studies pay heavy attention on knowledge absorption and knowledge transfer among firms, but less on the multifaceted and context dependent construct of mutual knowledge creation among firms in alliances. This study explains the concept of copoiesis as the genuine creation of joint knowledge among firms by referring to the socio-cognitive view and the structuration theory.
Keywords: M19; 650; Inter-organizational learning; Mutual knowledge creation; Structuration theory; Socio-cognitive view; Alliances